QSPR Analysis of certain Distance Based Topological Indices - Shirakol, Shailaja; Kalyanshetti, Manjula; Hosamani, Sunilkumar M. (Applied mathematics and nonlinear sciences, 2019)
In QSAR/QSPR study, topological indices are utilized to guess the bioactivity of chemical compounds. In this paper, we study the QSPR analysis of selected distance and degree-distance based topological indices. Our study reveals some important results which help us to characterize the useful topological indices based on their predicting power.